Posterior Pole Asymmetry Analysis with Optical Coherence Tomography - Kochendörfer, L.; Bauer, P.; Funk, J.; Töteberg-Harms, M. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: The aim of this study was to evaluate the reproducibility of the posterior pole asymmetry analysis (PPAA) in glaucomatous eyes and healthy controls in comparison to retinal nerve fiber layer measurements (RNFL) with spectral domain optical coherence tomography (SD-OCT).Patients and Methods: Prospectively, in a single session by one operator, three measurements were taken of the retinal thickness with the PPAA and three measurements of the RNFL with the eye-tracker function of the Heidelberg Spectralis SD-OCT.Results: The mean intraclass correlation coefficient (ICC) and lower confidence intervals (in parentheses) for PPAA were 0.98 (0.96) in both healthy (36 eyes) and glaucomatous eyes (26 eyes). Global coefficients of variation (COVs) were between 0.0 and 1.1 % in healthy controls and between 0.0 and 1.9 % in glaucoma eyes. Global ICCs for RNFL were 0.98 (0.96) in healthy controls and 0.98 (0.97) in glaucoma eyes and global COVs were between 0.0 and 6.8 % in healthy controls and between 0.0 and 3.0 % in glaucoma eyes.Conclusion: Reproducibility of the PPAA was good and exceeds that of established RNFL measurements. Thus, PPAA is an additional useful tool in management of glaucoma.
Keywords: optical coherence tomography; spectral-domain optical coherence tomography; SD-OCT; spectralis OCT; OCT; reproducibility; glaucoma; posterior pole asymmetry analysis